2019
DOI: 10.18187/pjsor.v15i3.2668
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of the COM-Poisson Distribution through the Mean Using Spectral Algorithms for Solving Nonlinear Equations

Abstract: The Poisson regression is popularly used to model count data. However, real data often do not satisfy the assumption of equality of the mean and variance which is an important property of the Poisson distribution. The Poisson – Gamma (Negative binomial) distribution and the recent Conway-Maxwell-Poisson (COM-Poisson) distributions are some of the proposed models for over- and under-dispersion respectively. Nevertheless, the parameterization of the COM-Poisson distribution still remains a major challenge in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
5
0
0
Order By: Relevance
“…This implies that marital status is a deciding factor to snail meat consumption in some households. This result also agrees with Adeniyi et al (2013) who reported that majority of the respondents were married (66.2 percent). Table 1 further reveals that a large percentage of the respondents (35.0%) are Artisans followed by those that are civil servants (23.3%), Farmers (20.8%), Traders (17.5%) and the unemployed respondents (3.3%).…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 92%
See 4 more Smart Citations
“…This implies that marital status is a deciding factor to snail meat consumption in some households. This result also agrees with Adeniyi et al (2013) who reported that majority of the respondents were married (66.2 percent). Table 1 further reveals that a large percentage of the respondents (35.0%) are Artisans followed by those that are civil servants (23.3%), Farmers (20.8%), Traders (17.5%) and the unemployed respondents (3.3%).…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 92%
“…Table 4 showed that the major problems/constraints associated with snail meat consumption in the study area were Price of snail, followed by financial constraint, unavailability all year round and cultural belief. This corroborates the report of Adeniyi et al, (2013) that scarcity (unavailability all year round), price and cultural belief were major factors hindering the consumption of food products.…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 91%
See 3 more Smart Citations